2005
DOI: 10.1007/s00436-005-1343-5
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the puparia of the housefly, Musca domestica (Diptera: Muscidae) and blowfly, Chrysomya megacephala (Diptera: Calliphoridae)

Abstract: Examination of the puparia of the housefly, Musca domestica L. and blowfly Chrysomya megacephala (F.), through scanning electron microscopy (SEM), revealed many differences in the profile of their morphology. Special attention was focused on puparial characteristics used to differentiate between the two fly species studied, and between other forensically important flies. Results of this study indicate that the housefly puparia are almost evenly rounded at both ends and the anterior spiracle bears six papillae.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 7 publications
(6 reference statements)
0
17
0
Order By: Relevance
“…Although the approximately 30 globules seen in L. cuprina puparia in this study is similar to another blow fly belonging to the same genus, Lucilia illustris (about 30 globules), it differs from the about 23 globules of Lucilia (Phaenicia) sericata or about 50 globules of Lucilia (Phaenicia) coeruleiviridis (Liu and Greenberg 1989). As for the pupal respiratory horn, the respiratory openings of L. cuprina are arranged vertically, whereas this differs from the oblique arrangement observed in the blow fly, Chrysomya megacephala (Siriwattanarungsee et al 2005). Keilin (1944) determined that these respiratory horns of coarctate pupae of Cyclorrhapha are formed by extensions of the spiracular chambers.…”
Section: Discussionmentioning
confidence: 43%
See 1 more Smart Citation
“…Although the approximately 30 globules seen in L. cuprina puparia in this study is similar to another blow fly belonging to the same genus, Lucilia illustris (about 30 globules), it differs from the about 23 globules of Lucilia (Phaenicia) sericata or about 50 globules of Lucilia (Phaenicia) coeruleiviridis (Liu and Greenberg 1989). As for the pupal respiratory horn, the respiratory openings of L. cuprina are arranged vertically, whereas this differs from the oblique arrangement observed in the blow fly, Chrysomya megacephala (Siriwattanarungsee et al 2005). Keilin (1944) determined that these respiratory horns of coarctate pupae of Cyclorrhapha are formed by extensions of the spiracular chambers.…”
Section: Discussionmentioning
confidence: 43%
“…Erzinclioglu (2000) revealed that examination of fly puparia with SEM provides many distinguishing details by which they can be identified and can subsequently be used as entomological evidence in forensic investigations. The use of SEM to discover characteristics used to identify fly puparia is evident within the literature (Kitching 1976;Liu and Greenberg 1989;Siriwattanarungsee et al 2005). Since the larval skin of the late third instar is contracted and formed into the puparium during the formation of the pupa, many larval characteristics are retained in the puparium that fit the same profile used for identifying the third instar.…”
Section: Discussionmentioning
confidence: 98%
“…In flies of the family Muscidae, the length of the respiratory horn and arrangement of papillae are found to be different in some species, as demonstrated in Ophyra by Skidmore (1985). Moreover, the arrangement and number of papillae observed on the respiratory horns markedly differ between puparia of the housefly Musca domestica L. and blowfly Chrysomya megacephala (F.) (Siriwattanarungsee et al 2005).…”
mentioning
confidence: 99%
“…Pupa stage: The pupa is mahogany brown to dark brown in color and coarctate and barrel shaped. Morphology of puparium has been studied widely under LM [29] and SEM [30][31][32][33][34][35]. A simply key to identify the puparium of some blow fly species of Thailand was summarized by Sukontason et al [29].…”
Section: Fig 1-lateral Views Of Medically Important Blow Fly Speciesmentioning
confidence: 99%
“…A simply key to identify the puparium of some blow fly species of Thailand was summarized by Sukontason et al [29]. The main characteristics for identification include body appearance (with or without tubercle), such as the 3 rd thoracic segment to 1 st abdominal segment, distance between right and left posterior spiracles, number of bubble membranes and papillae on the anterior spiracle [29][30][31][32][33][34][35].…”
Section: Fig 1-lateral Views Of Medically Important Blow Fly Speciesmentioning
confidence: 99%